Perlindungan Hukum Terhadap Peserta Jaminan Kesehatan Nasional Atas Layanan Kesehatan yang Tidak Berkualitas: Legal Protection for National Health Insurance (JKN) Participants in The Context of Substandard Healthcare Services - Wicaksono, Emirza Nur (Jurnal Hukum dan Etika Kesehatan, 2026)
The National Health Insurance (JKN) is a strategic program of the Indonesian government aimed at providing equitable and fair access to healthcare services. Although it has enrolled millions of participants, the quality of healthcare services received by participants remains a significant issue, including long queues, drug shortages, service discrimination, and alleged malpractice. This study aims to examine the legal protection of JKN participants who experience substandard healthcare services, as well as to identify challenges and solutions in its enforcement. A normative legal research method is employed, using both the statutory approach and the conceptual approach to analyze relevant legislation, legal doctrines, and fundamental concepts such as legal protection, the responsibilities of service providers, and standards of quality healthcare services. The results indicate that, normatively, legal protection for JKN participants is already regulated through various laws and regulations. However, the optimization of this protection still requires strengthening and clarification of regulations concerning service standards, complaint mechanisms, supervisory effectiveness, and inter-agency coordination so that the existing legal framework can function more effectively and ensure participants’ rights are fully guaranteed. Therefore, systematic regulatory reinforcement is needed, including the clarification of norms regarding the obligations of service providers, the formulation of simpler and measurable complaint and dispute resolution mechanisms, and the improvement of supervisory instruments and sanctions that provide legal certainty and enforceability.